Benefit and Challenge of Soy Plant-based Formula in Infant and Children - Vandenplas, Yvan; Hegar, Badriul (Indonesian Nutrition Association, 2020)
The first report of soy being administered to an infant is over 100 years old (1). Since the 1960s the composition of soy formula has been better adapted to the nutritional needs of infants and since 2000 infant formula based on soy fulfills European Directives and legislation for infant feeding.Soy infant formula contains a soy protein isolate (95% protein), and methionine, carnitine, taurine, iron, calcium phosphor and zinc are added. Heating destroys the anti-protease activity of soy for over 90 %. In 2016, soy infant formula was still 12% of the USA market and 25 % of infants were fed soy infant formula during their first years of life (2).